2020
DOI: 10.1002/cta.2840
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analysis method of fractional‐order buck–boost converter

Abstract: Summary In this paper, the equivalent small parameter method (ESPM) is used to establish the nonlinear mathematical model of the fractional‐order buck–boost converter in continuous current mode (CCM), and the analytical expression of approximate steady‐state period of converter state variable is obtained by using equivalent small parameter method and combining with harmonic balance principle. The Matlab/Simulink is used to construct the fractional‐order capacitance and inductance and to build the circuit model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…In recent publications [5], [12], [24] and [25], researchers designed FOC and FOI elements using physical RC or RL networks to perform measurements in laboratory setups. We have designed the same networks with the same specifications using the minimax approach and found that this results in more accurate networks with a lower number of components.…”
Section: Using the Minimax Model In Recent Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent publications [5], [12], [24] and [25], researchers designed FOC and FOI elements using physical RC or RL networks to perform measurements in laboratory setups. We have designed the same networks with the same specifications using the minimax approach and found that this results in more accurate networks with a lower number of components.…”
Section: Using the Minimax Model In Recent Applicationsmentioning
confidence: 99%
“…In [24] Fang and Wang designed a FO capacitor of order 0.95 (85.5), using Oustaloup's eighth-order network and obtained a maximum error =0.35 in the frequency range from 3Hz to 10kHz. With our minimax approximation, we obtained an eighth-order network with the same topology and the same bandwidth, but with a reduced error of =0.0044.…”
Section: Using the Minimax Model In Recent Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance and the very wide range of applications of the fractional models (described by the fractional derivatives) directed mathematicians and physicians to study the numerical and approximate solutions for fractional differential equations (FDEs) using many approximate techniques. We have a lot of examples for the applications of such kind of equations in our life as in fluid mechanics, [1][2][3] image processing, 4 biology, [5][6][7][8][9][10][11][12] engineering, [13][14][15] physics, [16][17][18][19][20] electrical circuits and filters, [21][22][23][24][25][26][27][28][29][30][31][32] and others. [33][34][35][36] Definition 1.…”
Section: Introductionmentioning
confidence: 99%
“…In [23,24], based on the circuit averaging technique, the mathematical models of the fractional-order buck-boost converter in CCM and DCM were established. The fractional-order buck-boost converter was further modeled and studied by the equivalent small parameter method and the Riemann-Liouville definition [25,26]. The modeling and analysis of fractional-order DC-DC converters such as buck, boost, and buck-boost under DCM and CCM were summarized in [27].…”
Section: Introductionmentioning
confidence: 99%